Case report: A rare case of massive peripheral nerve melanotic schwannoma and review of the literature - Wang, Han; Shi, Lin; Tian, Tong; Xian, Hang; Song, Zhao; Cong, Rui; Zhao, Rui (Frontiers in Neurology, 2023)
Melanotic schwannoma is a rare tumor with indeterminate biologic behavior and varying treatment recommendations. Just about 200 cases have been reported worldwide, in which that occurred in peripheral nerves has even less reported. Due to lack of the cognition of melanotic schwannoma, it is easily to be misdiagnosed and mistreatment in primary hospitals. Hereon, we presented a case of massive melanotic schwannoma growing in brachial plexus of an elderly male patient. Firstly, the patient underwent a left forearm tumor resection in local primary hospital because a painless lump which was found there in 2017, of which details remain unclear. After this operation, the patient developed symptoms of left median nerve injury. So, he came to our hospital and underwent the second operation. During this operation, we found a part of median nerve was absence at left forearm, and the remanent median nerve, form broken end to the elbow, was totally turn black, which accompanied with petroleum-like exudate. Losing the opportunity of nerve repair, the black nerve was removed extensively and thoroughly. Postoperative pathological diagnosis revealed the tumor was melanotic schwannoma. 4 years later, the tumor was recurrence again, which leaded to the paralysis of the whole left arm and severe nerve pain, the pulmonary metastasis of the tumor was detected at same time. The black nerve was resected again in our hospital, and the nerve pain was partially relieved after operation. To our knowledge, it is the first time to report a melanotic schwannoma case happened in the peripheral nerve trunk and then spread to whole brachial plexus. There were many questions worthy of discussion could be invited from this case, and we analyzed and discussed them based on the relevant literatures. In conclusion, we reported a rare case of melanotic schwannoma happened in brachial plexus, and illustrated the problems of the diagnosis and treatment of it based on the analysis of relevant literatures, which is helpful for the cognition of this rare nerve tumor.